Bladder Reconstruction with Human Amniotic Membrane in a Xenograft Rat Model: A Preclinical Study - Barski, Dimitri (Int J Med Sci, 2017)
Background: Human amniotic membranes (HAMs) are assumed to have a number of unique characteristics including durability, hypoallergenic and anti-inflammatory properties. Materials and Methods: Multilayer HAMs from caesarian sections were applied to repair defined bladder defects in male Sprague-Dawley rats. The animals were sacrificed at 7, 21 and 42 days after implantation. Bladder volume capacity after grafting was measured. Histological analyses were performed to asses a number of parameters including HAM degradation, inflammatory reaction, graft rejection and smooth muscle ingrowth. Results: One rat died from sepsis in the treated group. No severe complications or signs of leakage were observed. Bladder capacity did not change over time. The initially increased inflammation in the HAM group diminished significantly over time (p<0.05). No signs of HAM degradation were observed and smooth muscle staining increased over time. Conclusions: HAMs appear to be durable and hypoallergenic grafts. The assumed suitability for the reconstruction of urinary tract justifies further research on detailed immunological process in larger grafts.